UPACARA METATAH DALAM GEGURITAN PUJA KALAPATI TATTWA - I Wayan Adi Upadana (Widya Aksara, 2020)
Hinduism is supported by 3 (three) basic frameworks, namely tattwa (philosophy), moral (ethics), and ceremony (ritual). Each of the three basic frameworks does not stand alone, complementing each other so that the implementation of Hinduism can be perfect. Likewise, the implementation of the teachings of Hinduism, between the implementation of tattwa, ethics, and ceremonies must be balanced so that the prosperity of life in the world and moksa can be achieved. The source of these teachings is found in many of his major literary works in Balinese literary works, which in this case are in the Geguritan Puja Kalapati Tattwa manuscript. The ceremony was followed by the offer of mabeyakala and then praying to Sang Hyang Siwaraditya until the procession of the metatah ceremony was completed which was marked by holding a prayer at the mrajan's denial led by Ida Pandita.